The Ability of Problem Solving for Tenth Grade Student on Problem Based Learning About Web-Assisted from Students Independence (Universitas Negeri Semarang, 2020)
Mathematics learning is very important given in order to the students can have problem solving skills. This study aims to test the effectiveness of PBL assisted by the web on students' problem solving abilities and describe problem solving abilities in terms of student independence. This research is a type of quantitative and qualitative. The study was conducted in Bangsri 1 Public High School SMA Negeri 1 Bangsri in the 2018/2019 academic year. The research subjects were tenth grade students consisting of one experimental class with web-based PBL treatment and one control class. Then two people were selected for the category of high, medium and low independence. Hypothesis testing uses one-party t-test and average difference test. The results of the study showed that PBL was assisted by the web effective against students' problem solving abilities. Students with high independence criteria do not always have good problem solving skills, but they show a significant increase after working on practice questions. Students with moderate independence criteria also showed an increase in problem solving skills after working on practice questions. Whereas in the low independence criteria there are students with good cognitive abilities but the problem solving ability improvement is low.